Genetic divergence analysis of bougainvillea (Bougainvillea spp) cultivars using morphological markers - KUMAR, P PAVAN; JANAKIRAM, T; BHAT, K V; PRASAD, K V; JAIN, RITU (The Indian Journal of Agricultural Sciences, 2015)
A study was undertaken to analyze diversity among the bougainvillea (Bougainvillea spp.) cultivars using morphological markers. A total of 38 morphological descriptors of UPOV guidelines were recorded for hundred bougainvillea cultivars. Significant amount of variation was observed for all the descriptors, indicating that many of the cultivars were documented to be superior. The Neibour Joining (NJ) dendrogram based on morphological characters data separated the bougainvillea cultivars into 12 major clusters. Cluster-I exhibited as largest cluster compared to all other clusters comprising 49 cultivars. However, cluster II with 14 cultivars, cluster III with 12 cultivars, cluster XII with 7, cluster X with 6, cluster VII with 5 cluster IV with 2 and clusters no V, VI, VIII, IX, XI having only one cultivar in each case. It clearly grouped the cultivars of single and double type of bracts and also grouping based on pattern of variegation in leaves. PCA plot also grouped the cultivars as a fashion of NJ clusters however, it was unable to distinguish among the single bracted types in this method. This considerable amount of variation was due to the diversity in bougainvillea cultivars. On the basis of present investigation, these cultivars were grouped into different categories for different character, may be used effectively for identification of cultivars. Further, these cultivars can be used in crop improvement programme.